Stock Market Performance during COVID-19 Pandemic: A Systematic Literature Review - FITRIANA, Pingkan Mayosi; SAPUTRA, Jumadil; HALIM, Zairihan Abdul (Theoretical and Practical Research in Economic Fields; Vol 14 No 2 (2023): TPREF, Volume XIV, Issue 2(28), Winter 2023, 2023)
This study provides a comprehensive review using a systematic database to comprehend the pragmatic studies that examine the stock market performance during the COVID-19 pandemic. This study systematically searches and synthezises the results of stock market performance during COVID-19 to provide an overview of the current state of knowledge. The objectives of this study are (1) to investigate the impact of COVID-19 on stock market performance, (2) to analyse the reaction of the stock market during a pandemic, and (3) to identify the perspective and gaps for future research. This study employs a Systematic Literature Review (SLR) approach and follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The databases used are Scopus and Web of Science (WoS), covering a period of 2020 to 2023. The articles were identified using specific keywords and were screened based on predefined criteria. A total of 57 articles were included in this study for review. This study examined the impact of the COVID-19 pandemic on stock market returns and volatility. Also, the study examines the interconnectedness between global stock markets. In addition, it explored the potential of government response to mitigate the pandemic's effect on the stock market. The study found that the initial impact was felt in the short term and negatively impacted investor sentiment, but the stock markets began to stabilise and recover over time. The study's findings suggest that future research should not only concentrate on the short-term impact and correlation between the stock market and the pandemic but also their long-term impact.